Polyester digital printing fabric and preparation method thereof
Patent Information
- Application Number
- CN202611242072.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-17
- Publication Date
- 2026-11-03
AI Technical Summary
In existing polyester digital printing technology, it is difficult to achieve both anti-bleeding and hand feel improvement, resulting in problems such as blurred printed patterns, jagged lines, and hardened hand feel.
A pretreatment working solution containing nano-impermeable components, reactive hand feel regulating components, and crosslinking agents is applied to the surface of polyester base fabric, and a functional layer with an organic-inorganic interpenetrating network structure is formed through heat treatment to achieve physical barrier and chemical anchoring of ink droplets.
It achieves both high-definition printing and excellent hand feel, with controlled ink droplet spread, clear printed patterns, a soft and smooth feel, and excellent washability.
Smart Images

Figure CN123027752A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of textile dyeing and finishing engineering technology, and in particular to a polyester digital printing fabric and its preparation method. Background Technology
[0002] In recent years, with the deep penetration of digital printing technology into the textile industry, digital printing has gradually occupied an important position in the high-end fabric processing field due to its significant advantages such as no need for plate making, fast response speed, fewer color matching restrictions, and high pattern precision. In the digital processing system of polyester fabrics, disperse dye inks are one of the most mature application systems. However, polyester fiber, as a synthetic fiber with high crystallinity, high orientation, and a lack of polar functional groups on its surface, presents significant technical challenges to digital printing processes due to its inherent hydrophobicity and smooth surface.
[0003] During inkjet printing, tiny ink droplets impact the fabric surface with extremely high kinetic energy. Due to the hydrophobic properties of polyester fibers, the contact angle of the ink droplets is relatively large at the moment of contact, making it difficult to wet and spread instantly. More importantly, under the influence of capillary effect, the ink droplets tend to migrate uncontrollably along the warp and weft gaps in the fabric structure. This migration manifests microscopically as the diffusion of dye molecules towards the edges of the pattern, and macroscopically as blurred outlines and severely jagged lines in the printed pattern, a phenomenon commonly known in the industry as "bleeding" or "color bleeding." This defect is particularly fatal in printing fine lines, cloud patterns, and high-precision designs, greatly reducing the product's grade and added value.
[0004] To overcome the aforementioned drawbacks, existing technologies commonly employ the method of applying polymeric thickeners or pastes to the fabric before printing. The mechanism of this method lies in utilizing the physical barrier layer formed by the polymeric material on the fabric surface, which restricts the free flow of ink by increasing surface viscosity or blocking capillary channels between fibers. However, this physical barrier mechanism is often accompanied by serious side effects. To achieve the ideal anti-bleeding effect, a large amount of film-forming material is usually applied, which forms a continuous and rigid film on the fiber surface after drying. This film not only covers the original luster and softness of the fiber, resulting in a stiff, rough fabric feel and a tendency to peel off with a "shell-like" texture, but also easily shrinks and deforms during subsequent high-temperature steaming or baking processes, further affecting the dimensional stability of the print.
[0005] On the other hand, as consumers increasingly demand comfort in textiles, the "hand feel" of polyester fabrics has become a key indicator of their quality. To improve the hand feel, dyeing and printing companies often add softening finishing processes after printing or mix softeners into the pretreatment solution. However, conventional physical adsorption softeners, such as traditional dimethicone or amino silicone oil, mainly rely on intermolecular forces to adsorb onto the fiber surface, resulting in weak binding. During subsequent high-temperature and high-humidity steaming and fixing processes and vigorous washing, these softeners are prone to desorption and shedding, making it difficult to sustain the improved hand feel. Even more problematic is that the introduction of softeners often exacerbates the risk of ink bleeding. The lubricating effect of softeners reduces the frictional resistance on the fiber surface, but this actually provides a channel for ink droplet migration, significantly reducing the anti-bleeding effect. Furthermore, softener components that detach and enter the dye bath may contaminate the dye bath and even clog the precision nozzles of the printing machine, increasing equipment maintenance costs.
[0006] In summary, there is an irreconcilable contradiction between anti-bleeding and hand feel improvement in the existing polyester digital printing technology system. Anti-bleeding requires a dense and highly barrier film, which often leads to a hardened hand feel; hand feel improvement requires a smooth surface and flexible molecular chains, which easily induces bleeding. How to achieve synergistic effects between the two in a single process system and break the technical paradox of "hard anti-bleeding" and "soft hand feel" is the core technical bottleneck that urgently needs to be solved in this field. Summary of the Invention
[0007] This application provides a polyester digitally printed fabric and its preparation method, aiming to solve the technical problem of difficulty in achieving both anti-bleeding and hand feel in the existing polyester digital printing technology.
[0008] To achieve the above objectives, this application proposes a method for preparing polyester digitally printed fabric, the method comprising the following steps: A pretreatment working solution is applied to the surface of a polyester base fabric; the pretreatment working solution contains nano-impermeable components, reactive hand feel regulating components, and crosslinking agents; The base fabric after applying the pretreatment working solution is subjected to heat treatment, so that the nano-impermeable component and the reactive hand feel regulating component cross-link in situ on the surface of the base fabric to form a film, thereby forming a functional layer that is impermeable and improves hand feel. A base fabric with the aforementioned functional layer is subjected to digital printing to obtain a polyester digitally printed fabric.
[0009] In some embodiments, the weight percentage concentration of each component in the pretreatment working solution is as follows: 1.5% to 4.0% nano-impermeable component, 4.0% to 9.0% reactive feel-modifying component, 1.0% to 2.5% crosslinking agent, 0.5% to 1.2% penetrant, and the remainder is water.
[0010] In some embodiments, the nano-impermeable component is a nano-oxide sol, wherein the nano-oxide includes one or more of silicon dioxide, aluminum oxide, zinc oxide, and titanium dioxide, and the average particle size is 10 nm to 80 nm.
[0011] In some embodiments, the reactive feel-modifying component is a modified polysiloxane with reactive functional groups, wherein the reactive functional groups include at least one of epoxy, amino, carboxyl, mercapto, or hydroxyl groups.
[0012] In some embodiments, the crosslinking agent is a blocked isocyanate crosslinking agent or an amino resin crosslinking agent; the blocked isocyanate crosslinking agent includes at least one of butanone oxime, caprolactam, phenol or diethyl malonate; the amino resin crosslinking agent is a melamine-formaldehyde resin crosslinking agent.
[0013] In some embodiments, the application method is any one of padding, doctor blade coating or screen printing coating, and the liquid content of the polyester base fabric after application is controlled at 35% to 55%.
[0014] In some embodiments, the heat treatment includes sequential low-temperature pre-drying and high-temperature setting steps; the low-temperature pre-drying temperature is 80℃~95℃, and the time is 2min~4min; the endpoint of the low-temperature pre-drying stage is to control the moisture content of the polyester base fabric to drop to 8%~12%; the high-temperature setting temperature is 175℃~190℃, and the time is 30s~60s.
[0015] In some embodiments, gradient wind speed control is adopted in the heat treatment step: the wind speed of the hot air nozzle is controlled at 0.5m / s to 1.5m / s during the low-temperature pre-drying stage, and the wind speed is controlled at 2.0m / s to 4.0m / s during the high-temperature setting stage.
[0016] In some embodiments, after the digital printing process, the digitally printed fabric is subjected to high-temperature steaming for color fixing; the steaming temperature is 130℃~135℃ and the time is 20min~30min.
[0017] This application also provides a polyester digital printing fabric, which is prepared by the above method. The surface of the polyester digital printing fabric has a functional layer with a thickness of 0.5μm to 2.0μm. The functional layer is an organic-inorganic interpenetrating network structure formed by nano-impermeable components and reactive hand feel regulating components, and the penetration width of the printed lines is less than 0.05mm.
[0018] This application proposes a polyester digitally printed fabric and its preparation method. The preparation method includes the following steps: applying a pretreatment working solution to the surface of a polyester base fabric; the pretreatment working solution contains a nano-impermeable component, a reactive hand feel regulating component, and a crosslinking agent; heat-treating the base fabric after applying the pretreatment working solution, causing the nano-impermeable component and the reactive hand feel regulating component to crosslink in situ on the base fabric surface to form a film, creating a functional layer that provides impermeability and improved hand feel; and digitally printing the base fabric with the functional layer to obtain the polyester digitally printed fabric. This application's technical solution has the following beneficial effects: The technical solution of this application involves applying a specific pretreatment working liquid containing nano-anti-seepage components, reactive hand feel regulating components, and crosslinking agents to the surface of a polyester base fabric, and then performing a heat treatment process to form an organic-inorganic interpenetrating network structure functional layer in situ on the base fabric surface. This solution utilizes nanoparticles to construct a micro-rough structure to achieve physical anti-seepage, while simultaneously imparting a lasting soft hand feel to the fabric through the chemical anchoring of reactive softeners, achieving simultaneous and synergistic effects of high-definition printing and excellent hand feel. Attached Figure Description
[0019] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort, wherein: Figure 1 This is a schematic flowchart illustrating a method for preparing a polyester digitally printed fabric according to an embodiment of this application. Detailed Implementation
[0020] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of this application, and not all of the embodiments. Based on the embodiments of this application, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of this application.
[0021] It should be noted that, unless otherwise stated or limited, all directional indications (such as up, down, left, right, front, back, etc.) in the embodiments of this application are only used to explain the relative positional relationship and movement of each component in a certain specific posture (as shown in the figure). If the specific posture changes, the directional indication will also change accordingly.
[0022] It should also be noted that, unless otherwise stated or limited, when an element is referred to as "fixed to" or "set on" another element, it may be directly on the other element or there may be an intervening element present. When an element is referred to as "connected to" another element, it may be directly connected to the other element or there may be an intervening element present.
[0023] Furthermore, unless otherwise stated or limited, the descriptions involving "first," "second," etc., in this application are for descriptive purposes only and should not be construed as indicating or implying their relative importance or implicitly specifying the number of technical features indicated. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include at least one of that feature. Additionally, the technical solutions of the various embodiments can be combined with each other, but this must be based on the ability of a person skilled in the art to implement them. When the combination of technical solutions is contradictory or impossible to implement, such a combination of technical solutions should be considered non-existent and not within the scope of protection claimed in this application.
[0024] This application provides a method for preparing polyester digitally printed fabrics, aiming to solve the technical paradox of achieving both anti-bleeding and improved hand feel in the digital printing process of polyester fabrics. This method establishes a complete technical chain from microscopic interface design and film-forming kinetics control to macroscopic performance evaluation. Its core logic lies in: constructing a specific organic-inorganic composite pretreatment system to provide the material basis for interfacial reactions; subsequently, combining precise drying kinetics control to achieve ordered film formation of nanoparticles and softener molecules; and finally, utilizing in-situ crosslinking reactions to form a stable interpenetrating network structure.
[0025] See Figure 1 As shown, the preparation method mainly includes the following steps: Step S10: Apply a pretreatment working solution to the surface of the polyester base fabric.
[0026] This step is the material basis and functional prerequisite for the entire treatment method. The pretreatment working solution is not a simple physical mixture of additives, but a multiphase dispersion system with potential reactivity. This pretreatment working solution contains nano-impermeable components, reactive hand feel regulating components, and crosslinking agents.
[0027] In specific implementation, the technical solution of this application selects nano-oxide sol as the nano-anti-seepage component, preferably nano-silica sol. It is understandable that polyester fiber, as a hydrophobic synthetic fiber with high crystallinity and orientation, has a smooth surface and lacks active groups, making it highly susceptible to lateral wetting and diffusion after ink droplet impact. Nano-silica particles possess a large specific surface area (typically 200-400 m² / g) and abundant surface silanol (-Si-OH) active sites. When dispersed in the working solution, it can exist stably in sol form, forming a dispersion state between a true solution and a coarse dispersion system.
[0028] Its anti-seepage mechanism lies in the synergy of microscopic barrier effect and wetting angle hysteresis effect. When the working fluid is applied to the surface of polyester base fabric and dries to form a film, nanoparticles construct micron- or even submicron-scale rough structures in situ on the fiber surface. The contact angle hysteresis of droplets on the rough surface is mainly due to the blocking effect of the three-phase contact line. The protruding structure constructed by nanoparticles can effectively pin the three-phase contact line of the ink droplet, significantly increasing the energy barrier for droplet spreading, thereby inhibiting the lateral seepage of ink from a physical mechanism.
[0029] The average particle size of nanoparticles ranges from 10 nm to 80 nm. If the particle size is too small (<10 nm), the specific surface area is too large, resulting in extremely high surface energy. This leads to intense Brownian motion in the system, significantly increasing the probability of collisions between particles. Irreversible hard agglomeration easily occurs during the preparation or storage of the working solution, forming secondary particles and losing the nanoscale effect. Furthermore, stress concentration points are easily generated after film formation, increasing the film's brittleness and even causing pulverization and detachment during subsequent friction. If the particle size is too large (>80 nm), the particles settle faster in a gravitational field, resulting in poor dispersion stability. They are also prone to clogging the mesh during screen printing or detaching due to mechanical friction after padding, failing to form a continuous and dense impermeable layer. More importantly, large-diameter particles severely damage the hand feel, causing a rough, grainy texture on the fabric surface.
[0030] It should be noted that, in addition to nano-silica, the nano-impermeable components described in this application can also be one or more of nano-alumina, zinc oxide, or titanium dioxide sol. These nano-oxides also possess abundant surface hydroxyl groups and nanoscale effects, with their average particle size controlled within the range of 10 nm to 80 nm. Among them, nano-titanium oxide (titanium dioxide) and nano-alumina exhibit higher hardness, further enhancing the wear resistance of the impermeable layer; nano-zinc oxide possesses certain UV resistance. These nano-oxides function similarly to silica in constructing a microscopic rough structure and anchoring the three-phase contact line, all achieving impermeability.
[0031] Meanwhile, to address the hand feel issue, a reactive hand feel regulating component is introduced into the pretreatment working solution system, preferably a modified polysiloxane with epoxy or amino functional groups. The polysiloxane backbone is composed of silicon-oxygen bonds (-Si-O-), with large bond angles and long bond lengths, resulting in extremely flexible molecular chains that significantly reduce the coefficient of friction on the fiber surface, giving the fabric a smooth hand feel. However, while conventional amino-modified silicone oils offer excellent initial hand feel, their high polarity makes them prone to adsorbing nitrogen oxides from the air, leading to yellowing. Furthermore, their adsorption to polyester fibers relies solely on van der Waals forces, lacking chemical bonding and resulting in poor wash resistance.
[0032] This embodiment preferably uses terminal epoxy-modified polysiloxanes. The epoxy groups at the ends of the molecular chains are chemically inert at room temperature, ensuring the storage stability of the working solution. However, under high temperature and the action of a catalyst, the epoxy groups open the ring and react with crosslinking agents or fiber surface-active groups, achieving a balance between functionality and stability. This molecular design provides reactive sites for subsequent chemical anchoring.
[0033] In addition to the preferred epoxy and amino groups, modified polysiloxanes with reactive functional groups can also be carboxyl-modified, mercapto-modified, or hydroxyl-modified polysiloxanes. Carboxyl and hydroxyl groups also exhibit high reactivity, capable of undergoing esterification or urethane reactions with isocyanate groups released from blocked isocyanates at high temperatures, achieving chemical crosslinking. Mercapto groups can be bonded through thiol-olefin click chemistry or reactions with isocyanates. These functional groups all ensure the durable adhesion of the softener to the fiber surface.
[0034] The introduction of a crosslinking agent into the pretreatment working solution is a crucial bridge connecting the inorganic impermeable phase and the organic flexible phase, and is the core of achieving the interpenetrating network structure. This embodiment preferably uses a blocked isocyanate crosslinking agent. Isocyanate groups (-NCO) have extremely high reactivity, but in aqueous systems, they readily react with water to form urea, leading to gelation and storage failure. This application employs a blocking technology, utilizing a blocking agent (such as methyl ethyl ketone oxime, caprolactam, diethyl malonate, etc.) to combine with the -NCO groups to form an adduct. At room temperature, the isocyanate groups are blocked by the blocking agent, remaining in a latent inactive state, thus endowing the working solution with storage stability for several months. Only when the subsequent heat treatment temperature exceeds the deblocking temperature (usually greater than 150°C) does the blocking agent dissociate, releasing the highly reactive -NCO groups, instantly triggering the crosslinking reaction.
[0035] In the working solution, the weight percentage concentrations of each component are controlled as follows: nano-barrier component 1.5%–4.0%, reactive feel-modifying component 4.0%–9.0%, crosslinking agent 1.0%–2.5%, penetrant 0.5%–1.2%, with the remainder being water. If the nano-component is too low, a continuous barrier layer cannot be formed, resulting in microscopic pore defects; if it is too high, the coating will become more brittle, and the working solution viscosity will be too high, affecting penetration. The ratio of softener to crosslinking agent determines the crosslinking density and feel durability after film formation. If the crosslinking density is too low, the network structure is loose and not washable; if the crosslinking density is too high, the film modulus is too high, the feel becomes hard, and the softening improvement is lost.
[0036] During the application process, to ensure that the working fluid can uniformly cover the fiber surface, this embodiment employs methods such as padding, doctor blade coating, or screen printing coating. Taking the padding process as an example, the key control parameter is the amount of liquid carried. This application strictly controls the amount of liquid carried on the polyester base fabric after application to be between 35% and 55%. This value is determined based on a comprehensive consideration of film thickness and drying energy consumption, and also involves the migration dynamics of fluid in porous media.
[0037] It should be understood that, in addition to the padding process, the pretreatment working solution of this application can also be applied by doctor blade coating or screen printing coating. When using doctor blade coating or screen printing coating, the amount of liquid on the polyester base fabric after application (which can be referred to as the sizing rate here) also needs to be controlled between 35% and 55%. For doctor blade coating, the coating amount can be controlled by adjusting the doctor blade angle and blade pressure; for screen printing coating, the sizing rate can be controlled by selecting the mesh number (e.g., 80-120 mesh) and doctor blade speed to ensure the uniformity of the functional layer thickness.
[0038] Polyester fabrics are porous, and the working solution penetrates into the interfiber spaces through capillary action. If the liquid content is too low (<35%), it means the base fabric doesn't absorb enough working solution, resulting in an inability to form a continuous and complete functional layer after drying, leading to leaks and seepage prevention failure. Conversely, if the liquid content is too high (>55%), it not only wastes raw materials but also prolongs subsequent drying time and increases energy consumption. More seriously, excessive free water during drying easily causes solute migration due to capillary flow, leading to solutes in the working solution accumulating on the fabric surface or edges, resulting in uneven distribution and defects such as uneven color or darker edges and lighter centers. In practice, this parameter needs to be precisely controlled by adjusting the roller pressure (usually 2-4 kgf / cm²) and speed to ensure the working solution adheres evenly to the surface of each fiber.
[0039] To ensure the stability of the multiphase system during actual preparation, the following simplified procedure should be followed: First, add some deionized water and penetrant to the reactor, and then slowly add nano-silica sol under stirring for pre-dispersion; subsequently, add epoxy-terminated modified polysiloxane for emulsification and dispersion; finally, add pre-diluted blocked isocyanate crosslinking agent, and adjust the pH of the system to weakly acidic (pH 5.0-6.5) to maintain system stability. Add water and stir at low speed until homogeneous. This preparation process is simple and controllable, suitable for industrial production.
[0040] Step S20: Heat-treat the base fabric after applying the pretreatment working solution to allow the nano-impermeable components and reactive hand feel regulating components to cross-link in situ on the surface of the base fabric to form a functional layer that provides impermeability and improved hand feel.
[0041] This step is the core of achieving functional transformation, involving a complex coupling process of drying kinetics and chemical reaction kinetics. Drying is not merely the removal of moisture, but also the process of forming and fixing the film structure. If the traditional high-temperature rapid drying process is used, the surface moisture evaporates instantly to form a dense hardened layer, blocking the channels for internal moisture to diffuse outward, causing a sudden increase in internal vapor pressure. This leads to defects such as film blistering and rupture, as well as additive migration, severely affecting the film quality.
[0042] To address this critical issue, this application proposes a refined heat treatment process based on moisture content feedback control and gradient wind speed adjustment. In practice, the heat treatment process is designed to consist of two sequential stages: low-temperature pre-drying and high-temperature setting.
[0043] The first stage is low-temperature pre-drying. The temperature is set between 80℃ and 95℃ for 2 to 4 minutes. This temperature range falls within the linear region of the moisture evaporation rate curve, enabling gentle moisture removal. During this process, the moisture content of the polyester base fabric is controlled to decrease to 8% to 12%. When the moisture content drops to this range, the slurry on the fiber surface undergoes a phase transition, changing from a liquid state to a semi-dry gel state. In the gel state, the movement of nanoparticles and softener macromolecules is restricted, and they begin to form a pre-oriented arrangement structure, but the molecular chain segments still have a certain degree of mobility. If the moisture content is too high (>12%) and the process proceeds directly to high temperature, the large amount of residual free water will instantly vaporize, expanding in volume by more than a thousand times, exerting a huge impact on the unformed film layer and disrupting the continuity of the film structure. If the pre-drying transitions to complete drying (moisture content <8%), the molecular chains lock in their positions too early, forming a rigid network, which is not conducive to the diffusion of reactive molecular segments during subsequent cross-linking reactions, resulting in insufficient cross-linking density and decreased wash resistance.
[0044] To further optimize drying uniformity, this embodiment employs a gradient airflow control strategy in the heat treatment step. During the low-temperature pre-drying stage, the airflow velocity of the hot air nozzles is controlled at 0.5 m / s to 1.5 m / s. This lower airflow velocity is designed to avoid shear damage to the wetted film surface caused by high-velocity airflow. According to boundary layer theory, high airflow velocity thins the flow boundary layer on the fabric surface, improving heat and mass transfer efficiency, but it also increases fluid shear force, easily causing localized thickness unevenness or orange peel-like surface phenomena. This embodiment uses mild, laminar flow hot air to ensure that the rate of moisture diffusion from the fabric interior to the exterior remains balanced with the rate of surface evaporation, eliminating the risk of surface hardening and laying a uniform microscopic foundation for the formation of the functional layer.
[0045] After pre-drying, the base fabric enters the high-temperature setting stage. The temperature rapidly rises to 175℃~190℃ for 30 s~60 s. The physical significance of this stage is to quickly remove residual moisture and trigger the in-situ crosslinking film-forming reaction. For blocked isocyanate crosslinking agents, this temperature range is sufficient to overcome the deblocking activation energy, causing the blocking agent to dissociate. The released -NCO groups instantly react chemically with the silanol groups on the surface of nano-silica, the functional groups on the modified polysiloxane, and the trace end groups on the surface of polyester fibers.
[0046] This process constructs a unique organic-inorganic interpenetrating network structure. Nano-silica particles, acting as the inorganic hard phase, are uniformly dispersed and anchored within the network framework, providing the micro-nano structural support required for seepage prevention. Modified polysiloxanes, acting as the organic soft phase, fill the network gaps and coat the fibers, providing improved hand feel. This network structure achieves functional synergy: on the one hand, the inorganic network protects the organic softener from being easily washed away; on the other hand, the organic network alleviates the brittleness of the inorganic coating. Through chemical bonding, the functional layers are firmly bonded to the polyester base fabric surface, significantly improving the problems of poor adhesion and washability inherent in traditional physical coatings.
[0047] During the high-temperature setting stage, to enhance heat exchange efficiency and rapidly remove small molecule volatiles generated during desealing, the wind speed is controlled to be increased to 2.0 m / s to 4.0 m / s. The turbulent boundary layer formed by the high wind speed can significantly improve heat and mass transfer efficiency, ensuring rapid and thorough cross-linking reaction and forming a highly cross-linked, dense functional layer.
[0048] Step S30: Digitally print the base fabric with the functional layer to obtain a polyester digitally printed fabric.
[0049] After the refined processing in steps S1 and S20, a functional layer with a specific microstructure and chemical activity has been constructed on the surface of the polyester base fabric. Step S30, as a key post-processing step, focuses on using digital inkjet technology to achieve precise and controlled deposition of dye ink on the surface of the functional layer.
[0050] Digital printing is a complex fluid dynamics process involving fluid impaction, wetting and spreading, and penetration and diffusion. At the microscopic scale, ink droplets are ejected from the nozzle at a speed of 4–8 m / s and impact the fabric surface. For untreated polyester base fabrics, due to their low surface energy and smoothness, the ink droplets are prone to droplet deformation and splashing or lateral wetting and diffusion after impact.
[0051] In the functional layer constructed in this application, the behavior of ink droplets is fundamentally altered. Due to the micro-nano rough structure constructed by nano-silica particles in the functional layer, ink droplets encounter enormous solid-liquid interfacial resistance upon impact. This micro-nano structure, composed of countless nanoscale protrusions, effectively anchors the three-phase contact line of the ink droplet. According to the contact hysteresis theory, when the ink droplet attempts to spread forward, it needs to overcome a huge energy barrier, thereby blocking the seepage path and achieving physical barrier against seepage.
[0052] Meanwhile, the presence of reactive polysiloxanes modulates the surface energy distribution on the fiber surface. The ink spreading behavior is driven by the solid-liquid interfacial energy difference. If the surface is too hydrophobic and the contact angle is too large, ink droplets are difficult to adhere, resulting in white spots or poor leveling, leading to dotted color defects in the pattern; if the surface is too hydrophilic and the contact angle is too small, severe bleeding occurs. This application, through precise formulation design, utilizes the organic-inorganic composite effect to keep the surface energy of the functional layer within a specific equilibrium range (critical surface tension of approximately 30-40 mN / m), ensuring that ink droplets can adhere smoothly to the wet surface without ink repulsion, while strictly limiting excessive lateral flow.
[0053] In practice, disperse dye ink is selected as the printing paste. Disperse dye ink contains micron-sized dye particles, dispersants, humectants, and deionized water. The nozzle diameter of an inkjet printhead is typically between 20 and 50 microns, requiring the ink system to possess excellent dispersion stability. Due to the immediate fixing effect of the functional layer on the ink, the ink droplets stabilize rapidly after impact, effectively suppressing the fusion and color mixing of adjacent droplets.
[0054] For printing intricate patterns, this embodiment further optimizes the inkjet parameters. For high-precision lines (line width < 0.5 mm), a unidirectional printing mode is used to reduce the back-and-forth error of the printing press, and the inkjet volume is controlled at 8–12 g / m² to prevent exceeding the ink penetration threshold due to excessive ink volume. For large areas of color blocks, a bidirectional high-speed printing mode is used, with the inkjet volume controlled at 15–25 g / m². Due to the excellent ink penetration resistance of the functional layer, even high-saturation color block printing maintains sharp and clear edges without smudging. Furthermore, the functional layer improves the ink drying speed, preventing smudging during the printing process.
[0055] Step S40: Perform high-temperature steaming to fix the color of the digitally printed fabric.
[0056] Steaming and color fixing are crucial steps in polyester digital printing, determining dye uptake and color fastness. Under high temperature and humidity, disperse dye molecules gain sufficient kinetic energy to overcome the energy barrier on the fiber surface, diffusing and fixing into the polyester fiber. This step not only requires successful dye uptake but also demands that the functional layer remain stable under harsh, humid conditions.
[0057] In practice, the vaporization temperature is set to 130℃~135℃, and the time is 20 min~30 min. This temperature range is at or slightly above the glass transition temperature of polyester fibers. At this temperature, the fiber macromolecular chain segments begin to move, the internal free volume increases, and a channel is provided for the diffusion of dye molecules.
[0058] In this step, the functional layer constructed in this application exhibits a unique heat shielding effect and diffusion channel maintenance characteristics. Due to the in-situ crosslinking technology employed in the functional layer, its crosslinked network demonstrates excellent thermal stability at high temperatures. The nano-silica particles, acting as an inorganic framework, exhibit significantly better heat resistance than organic polymers, effectively preventing excessive shrinkage or deformation of the fibers in high-temperature steam environments and ensuring the dimensional stability of the fabric.
[0059] During the steaming process, the functional layer does not hinder dye diffusion. Although the functional layer forms a network structure on the fiber surface, its interpenetrating network has a rich microporous structure, allowing small dye molecules to pass through. On the contrary, due to the enrichment effect of the functional layer on the ink, the local concentration of dye on the fiber surface is relatively high. This increases the concentration gradient driving force for dye diffusion into the fiber interior, resulting in increased color yield and more vibrant and uniform color in the fabric.
[0060] More importantly, in high-temperature and high-humidity environments, traditional physical adsorption coatings are prone to softening, peeling, or dissolving, leading to loss of hand feel or contamination of the guide rollers. However, the organic-inorganic interpenetrating network structure in this application exhibits excellent resistance to high-temperature steam and condensate due to its chemical bonding properties. The functional layer remains firmly attached to the fiber surface, protecting the internal softener molecules from hydrolysis or washout. After steaming, the fabric surface does not require further softening treatment, directly achieving a durable, soft, and smooth hand feel, thus integrating the printing and finishing processes.
[0061] Further processing includes subsequent washing to remove surface dye; this process is simple and will not be detailed here. The final polyester digitally printed fabric has a surface functional layer thickness of 0.5 μm to 2.0 μm. This thickness range ensures both waterproofing and a pleasant hand feel without compromising the fabric's breathability and drape. In terms of macroscopic performance, the printed lines exhibit a high precision standard with a penetration width of less than 0.05 mm, and the fabric has a soft, smooth hand feel and excellent wash resistance.
[0062] To further verify the effectiveness of the technical solution of the present invention, the following detailed description is provided in conjunction with specific preparation examples and comparative examples.
[0063] Example 1 A method for preparing a polyester digitally printed fabric includes the following steps: (1) Preparation of pretreatment working solution: Weigh 3.0 kg of nano-silica sol with an average particle size of 30 nm, 6.0 kg of epoxy-terminated modified polysiloxane, 1.5 kg of TDI prepolymer crosslinking agent blocked by methyl ethyl ketone oxime, and 0.8 kg of fatty alcohol polyoxyethylene ether penetrant, and add deionized water to make up to 100 kg. Stir at 800 rpm for 30 minutes in a disperser to obtain a uniform emulsion.
[0064] (2) Apply working fluid: The polyester taffeta base fabric with a specification of 150T is passed through the impregnation machine, the pressure of the impregnation machine is controlled at 3.0 kgf / cm², the speed is 50 m / min, and the liquid content is measured to be 45%.
[0065] (3) Heat treatment: The impregnated base fabric is fed into the setting machine. The first stage is low-temperature pre-drying at 90℃ for 3 min, and the moisture content of the base fabric is controlled to drop to 10% by monitoring with an online infrared moisture meter. The wind speed is controlled at 1.0 m / s during this stage. The second stage is high-temperature setting at 180℃ for 45 s. The wind speed is controlled at 3.0 m / s during this stage.
[0066] (4) Digital printing: Using disperse dye ink, digital inkjet printing is performed on the pretreated base fabric, and the pattern contains fine lines 0.5 mm wide.
[0067] (5) Steaming and fixing: The printed fabric is steamed at 132°C for 25 minutes, then washed and fixed to obtain the finished product.
[0068] Example 2 The difference from Example 1 is that the average particle size of the nano silica sol is 10 nm and the amount used is 4.0 kg.
[0069] Example 3 The difference from Example 1 is that the average particle size of the nano silica sol is 80 nm and the amount used is 1.5 kg.
[0070] Example 4 The difference from Example 1 is that the reactive feel-modifying component is amino polyether block-modified silicone oil, and the amount used is 9.0 kg.
[0071] Example 5 The difference from Example 1 is that the crosslinking agent is caprolactam-blocked MDI prepolymer, and the amount used is 2.5 kg.
[0072] Example 6 The difference from Example 1 is that in the heat treatment step, the low-temperature pre-baking temperature is 80°C and the time is 2 min; the high-temperature setting temperature is 175°C and the time is 60 s.
[0073] Example 7 The difference from Example 1 is that in the heat treatment step, the low-temperature pre-baking temperature is 95°C and the time is 4 min; the high-temperature setting temperature is 190°C and the time is 30 s.
[0074] Example 8 The difference from Example 1 is that the moisture content of the base fabric is reduced to 8% at the end of the low-temperature pre-drying stage.
[0075] Example 9 The difference from Example 1 is that the moisture content of the base fabric is reduced to 12% at the end of the low-temperature pre-drying stage.
[0076] Example 10 The difference from Example 1 is that the wind speed in the low-temperature pre-drying stage is 0.5 m / s, and the wind speed in the high-temperature setting stage is 2.0 m / s.
[0077] Example 11 The difference from Example 1 is that the wind speed in the low-temperature pre-drying stage is 1.5 m / s and the wind speed in the high-temperature setting stage is 4.0 m / s.
[0078] Example 12 The difference from Example 1 is that the nano-impermeable component is replaced with nano-alumina sol with an average particle size of 30 nm, and the amount used is 3.0 kg. The remaining components and process parameters are the same as in Example 1.
[0079] Example 13 The difference from Example 1 is that the nano-impermeable component is replaced with nano-zinc oxide sol with an average particle size of 40 nm, and the amount used is 2.5 kg. The remaining components and process parameters are the same as in Example 1.
[0080] Example 14 The difference from Example 1 is that the nano-impermeable component is replaced with nano-titanium dioxide sol with an average particle size of 50 nm, and the amount used is 3.5 kg. The remaining components and process parameters are the same as in Example 1.
[0081] Example 15 The difference from Example 1 is that the nano-impermeable component is replaced with a mixed oxide sol (composed of nano-silica and nano-alumina in a 1:1 mass ratio, with an average particle size of 30 nm), and the total amount used is 3.0 kg. The remaining components and process parameters are the same as in Example 1.
[0082] Example 16 The difference from Example 1 is that the reactive feel-modifying component is replaced with a carboxyl-terminated modified polysiloxane, used in an amount of 6.0 kg. The remaining components and process parameters are the same as in Example 1.
[0083] Example 17 The difference from Example 1 is that the crosslinking agent is replaced with phenol-blocked MDI (diphenylmethane diisocyanate) prepolymer, and the amount used is 1.8 kg. The remaining components and process parameters are the same as in Example 1.
[0084] Example 18 The difference from Example 1 is that the crosslinking agent is replaced with hexamethylol melamine resin (amino resin crosslinking agent), with a dosage of 2.0 kg, and the pH of the working solution is adjusted accordingly to 4.5-5.5 to suit the curing conditions of amino resin. The remaining components and process parameters are the same as in Example 1.
[0085] Example 19 The difference from Example 1 is that the application method is changed to screen printing coating. A 100-mesh screen is used to evenly coat the pretreatment working solution onto the surface of the polyester base fabric, controlling the sizing rate to 40%. Subsequent heat treatment and printing steps are the same as in Example 1.
[0086] Comparative Example 1 The traditional sodium alginate sizing process is adopted. A 6% sodium alginate solution is evenly coated onto the surface of a polyester base fabric of the same specification, dried, and then subjected to digital printing and steam washing.
[0087] Comparative Example 2 No nano-impermeable components were added to the pretreatment working solution, and the remaining steps were the same as in Example 1.
[0088] Comparative Example 3 No crosslinking agent was added to the pretreatment working solution, and the remaining steps were the same as in Example 1.
[0089] Comparative Example 4 The traditional high-temperature rapid drying process was adopted, and the product was directly dried at 180°C without low-temperature pre-drying or moisture content control. The remaining steps were the same as in Example 1.
[0090] Performance testing and results analysis: The fabrics obtained in Examples 1-19 and Comparative Examples 1-4 were subjected to performance tests.
[0091] Bleeding width test: Use a high-magnification electron microscope to observe the edge of the printed lines and measure the maximum diffusion value of the line width.
[0092] Hand feel assessment: The HTY-03 fabric stiffness tester was used to test and calculate the bending length. The smaller the value, the softer the hand feel.
[0093] Washability test: The washing test was conducted according to GB / T 3921 standard, and the change rate of penetration width after 5 washes was tested.
[0094] Functional layer thickness: measured by scanning electron microscopy (SEM) sections.
[0095] The test results are shown in Table 1.
[0096] Table 1 Performance test data for each embodiment and comparative example
[0097] Results analysis: As shown in Table 1, the polyester digital printing fabrics prepared in Examples 1-11 of this application have a diffusion width controlled below 0.05 mm, which meets the standard for high-definition printing. At the same time, the bending length is about 2.1 cm, showing excellent soft hand feel. In the washability test, the diffusion width change rate is extremely low, proving that the functional layer is firmly bonded.
[0098] The specific analysis is as follows: Verification of the synergistic mechanism between seepage prevention and tactile feel: Comparing Example 1 with Comparative Examples 1 and 2, it can be seen that although Comparative Example 1 (traditional sizing) has a certain anti-seepage effect, the hand feel is extremely poor (bending length 4.5 cm); Comparative Example 2 (without seepage aid) has a passable hand feel, but severe seepage (0.20 mm). Only Example 1 of this application achieves both low seepage and a soft hand feel simultaneously through the synergistic effect of the physical pinning of nanoparticles and the chemical anchoring of reactive softener.
[0099] Verification of the effectiveness of in-situ crosslinking film formation: Comparing Example 1 and Comparative Example 3, it can be seen that although the initial performance was acceptable when the crosslinking agent was absent, the permeation change rate was as high as 8.5% after washing with water, indicating that the functional layer lacking chemical bonding was easily lost in subsequent processing. This directly verifies the necessity of unblocking and crosslinking the blocked isocyanate at high temperature to construct an interpenetrating network structure in this application.
[0100] Key validation of drying kinetics control: Comparing Example 1 and Comparative Example 4, it can be seen that when low-temperature pre-drying and moisture content control are cancelled, and high-temperature rapid drying is performed directly, the penetration width deteriorates to 0.08 mm, and the feel also becomes worse. This is because excessively rapid drying leads to uneven stress release within the film layer, resulting in microscopic bubbling, rupture, or additive migration, thus disrupting the continuity of film formation. This demonstrates that the moisture content feedback control and gradient wind speed adjustment process proposed in this application are crucial for ensuring film quality.
[0101] Sensitivity analysis of process parameters: Comparing Examples 1 with Examples 8 and 9, it can be seen that when the moisture content at the end of the pre-drying deviates from the optimal range of 8% to 12%, the film quality decreases slightly, but is still better than the comparative example. This indicates that this parameter range is the optimal window for film-forming phase transition.
[0102] Verification of the universality of nano-impermeable components: Examples 12-15 used nano-alumina, zinc oxide, titanium dioxide, and mixtures thereof to replace silica, respectively. Test results showed that the penetration width of the above examples was controlled below 0.05 mm, and the wash resistance remained at an excellent level of 1.0%-1.3%. This demonstrates the universality of the anti-penetration mechanism constructed in this application—namely, "anchoring the three-phase contact line of ink droplets by constructing a micro-rough structure through nanoparticles." Like silica, alumina, zinc oxide, and titanium dioxide all possess high specific surface area and surface hydroxyl groups, enabling them to form effective physical barriers and micro-pinning structures during the drying and film-forming process. The flexural strength of Examples 12 and 14 (alumina and titanium dioxide) slightly increased to 2.3 cm, possibly because the Mohs hardness of these two oxides is slightly higher than that of silica, which is slightly reflected in the micron-level feel, but still within an acceptable range. Example 15 (mixture) exhibited a synergistic effect, achieving a good balance between anti-penetration and feel.
[0103] Verification of the diversity of reactive feel-modifying components and crosslinking systems: Examples 16-18 tested carboxyl-modified silicone oil, phenol blocking crosslinking agent, and amino resin crosslinking agent systems, respectively. Example 16 (carboxyl-modified silicone oil): Its performance was basically the same as that of Example 1 (epoxy-based silicone oil), proving that polysiloxanes with reactive functional groups (such as carboxyl, amino, and epoxy groups) can be chemically anchored through the crosslinking network of this application, solving the problem of easy detachment of traditional silicone oils.
[0104] Example 17 (phenol blocking): The blocking effect was comparable to that of methyl ethyl ketone oxime, indicating that different types of blocking agents can successfully release -NCO groups for crosslinking as long as the unblocking temperature is matched (both should be in the range of 175℃-190℃).
[0105] Example 18 (Amino Resin): Exhibiting a lower percolation rate (0.8%), indicating that the network formed by the amino resin, fibers, and nanoparticles is extremely dense and exhibits excellent wash resistance. Although it feels slightly stiff (bending length 2.4 cm), it has unique advantages in resisting harsh washing scenarios. This verifies the feasibility and necessity of the "amino resin crosslinking agent" in claim 5.
[0106] Process adaptability verification of the application method: Example 19 employs a screen printing coating process instead of a padding process. All performance indicators of Example 19 meet the high standards of this application (bleed width 0.04 mm, hand feel 2.1 cm). This demonstrates that the technical solution of this application is not limited to the padding process. By controlling the sizing rate (equivalent to liquid content) of the screen printing within the range of 35%-55%, a uniform and continuous organic-inorganic interpenetrating network functional layer can also be formed. This result broadens the industrial application scenarios of this invention, making it particularly suitable for partial printing or processing of thick fabrics requiring higher liquid content.
[0107] Through comprehensive testing in Examples 1-19, the breadth and effectiveness of the types of nano-oxides, reactive functional groups, crosslinking agents, and application methods covered in the claims of this application were fully verified. No negative results were observed in any of the variant examples, and their performance was superior to the comparative examples, strongly supporting the rationality of the scope of protection of the claims. This invention, through specific formulation design and process control, successfully breaks through the technical barrier of the incompatibility between anti-bleeding and hand feel in polyester digital printing.
[0108] The above description is only a part or preferred embodiment of this application. Neither the text nor the drawings should limit the scope of protection of this application. All equivalent structural transformations made using the content of this application's specification and drawings under the overall concept of this application, or direct / indirect applications in other related technical fields, are included within the scope of protection of this application.
Claims
1. A method for preparing a polyester digitally printed fabric, characterized in that, Includes the following steps: Apply a pretreatment working solution to the surface of the polyester base fabric; The pretreatment working solution contains nano-impermeable components, reactive feel-modifying components, and crosslinking agents; The base fabric after applying the pretreatment working solution is subjected to heat treatment, so that the nano-impermeable component and the reactive hand feel regulating component cross-link in situ on the surface of the base fabric to form a film, thereby forming a functional layer that is impermeable and improves hand feel. A base fabric with the aforementioned functional layer is subjected to digital printing to obtain a polyester digitally printed fabric.
2. The method for preparing polyester digitally printed fabric according to claim 1, characterized in that, The weight percentage concentrations of each component in the pretreatment working solution are as follows: 1.5%–4.0% nano-impermeable component, 4.0%–9.0% reactive feel-modifying component, 1.0%–2.5% crosslinking agent, 0.5%–1.2% penetrant, and the remainder is water.
3. The method for preparing polyester digitally printed fabric according to claim 1 or 2, characterized in that, The nano-impermeable component is a nano-oxide sol, and the nano-oxide includes one or more of silicon dioxide, aluminum oxide, zinc oxide, and titanium dioxide, with an average particle size of 10 nm to 80 nm.
4. The method for preparing polyester digitally printed fabric according to claim 1 or 2, characterized in that, The reactive feel-modifying component is a modified polysiloxane with reactive functional groups, wherein the reactive functional groups include at least one of epoxy, amino, carboxyl, mercapto, or hydroxyl groups.
5. The method for preparing polyester digitally printed fabric according to claim 1 or 2, characterized in that, The crosslinking agent is a blocked isocyanate crosslinking agent or an amino resin crosslinking agent; the blocked isocyanate crosslinking agent includes at least one of butanone oxime, caprolactam, phenol or diethyl malonate; the amino resin crosslinking agent is a melamine-formaldehyde resin crosslinking agent.
6. The method for preparing polyester digitally printed fabric according to claim 1, characterized in that, The application method is any one of padding, blade coating or screen printing coating, and the liquid content of the polyester base fabric after application is controlled at 35% to 55%.
7. The method for preparing polyester digitally printed fabric according to claim 1, characterized in that, The heat treatment includes sequential low-temperature pre-drying and high-temperature setting steps; the low-temperature pre-drying temperature is 80℃~95℃, and the time is 2min~4min; the endpoint of the low-temperature pre-drying stage is to control the moisture content of the polyester base fabric to drop to 8%~12%; the high-temperature setting temperature is 175℃~190℃, and the time is 30s~60s.
8. The method for preparing polyester digitally printed fabric according to claim 7, characterized in that, In the heat treatment steps, gradient wind speed control is adopted: the wind speed of the hot air nozzle is controlled at 0.5m / s to 1.5m / s during the low temperature pre-drying stage, and the wind speed is controlled at 2.0m / s to 4.0m / s during the high temperature setting stage.
9. The method for preparing polyester digitally printed fabric according to claim 1, characterized in that, After the digital printing process, the digitally printed fabric is subjected to high-temperature steaming for color fixing; the steaming temperature is 130℃~135℃ and the time is 20min~30min.
10. A polyester digital printing fabric, characterized in that, The polyester digitally printed fabric, prepared by any one of claims 1 to 9, has a functional layer with a thickness of 0.5 μm to 2.0 μm on its surface. The functional layer is an organic-inorganic interpenetrating network structure formed by nano-impermeable components and reactive hand feel regulating components, and the penetration width of the printed lines is less than 0.05 mm.
